The embarrassment of being human: A critique of new materialism and object‐oriented ontology. (June 2018) - Boysen, Benjamin
Abstract : New materialism and object‐oriented ontology have recently gained widespread attention. Taking as exemplary the work of Jane Bennett and Graham Harman (yet also drawing on other figures within these materialist fields), this paper argues that the theories are self‐contradictory and rooted in what I label semiophobia (an unease with human reality as embedded in a semiotic reality). In addition, I argue that Harman's poetics (weird realism) and Bennett's strategic anthropomorphism are inconsistent and fail to deliver what they promise. Finally, I argue that in spite of its honorable intentions new materialism entails undesirable ethical and political consequences.